Implementasi Kebijakan Pemerintah Daerah Tentang Relokasi Pasar Rada Mata ke Pasar Oba Komi(Studi pada Dinas Perdagangan dan Perindustrian Kabupaten Sumba Barat Daya) - Soleman Renda Bili; Bewa Dangu Wole; Samuel Bora Lero (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
The policy of relocating the market from Rada Mata market to Oba Komi market permanently aims to organize a better and cleaner city because the existence of Rada Mata market raises several problems, the first is the narrow location of the market, the place is not strategic, the existence of gas stations, and access to highways leading to the airport and the port which results in traffic congestion. The policy of the Southwest Sumba Regency government is a good solution, but in the implementation of the policy is not optimal, there is no firmness from the government to continue implementing the existing decision but what happens is all traders return to selling in the relocated market. Type of Qualitative Research. This study aims to determine, analyze the supporting and inhibiting factors in the implementation of the Regional Government policy on the relocation of the Rada Mata market to the Oba Komi marke.